GhLUX1 and GhELF3 Are Two Components of the Circadian Clock That Regulate Flowering Time of Gossypium hirsutum - Hao, Pengbo; Wu, Aimin; Chen, Pengyun; Wang, Hantao; Ma, Liang; Wei, Hengling; Yu, Shuxun (Frontiers in Plant Science, 2021)
Photoperiod is an important external factor that regulates flowering time, the core mechanism of which lies in the circadian clock-controlled expression of FLOWERING LOCUS T (FT) and its upstream regulators. However, the roles of the circadian clock in regulating cotton flowering time are largely unknown. In this study, we cloned two circadian clock genes in cotton, GhLUX1 and GhELF3. The physicochemical and structural properties of their putative proteins could satisfy the prerequisites for the interaction between them, which was proved by yeast two-hybrid (Y2H) and Bimolecular Fluorescent Complimentary (BiFC) assays. Phylogenetic analysis of LUXs and ELF3s indicated that the origin of LUXs was earlier than that of ELF3s, but ELF3s were more divergent and might perform more diverse functions. GhLUX1, GhELF3, GhCOL1 and GhFT exhibited rhythmic expression and were differentially expressed in the early-flowering and late-flowering cotton varieties under different photoperiod conditions. Both overexpression of GhLUX1 and overexpression of GhELF3 in Arabidopsis delayed flowering probably by changing the oscillation phases and amplitudes of the key genes in the photoperiodic flowering pathway. Both silencing of GhLUX1 and silencing of GhELF3 in cotton increased the expression of GhCOL1 and GhFT and resulted in early flowering. In summary, the circadian clock genes were involved in regulating cotton flowering time and could be the candidate targets for breeding early-maturing cotton varieties.